2020
DOI: 10.3390/jrfm13050092
|View full text |Cite
|
Sign up to set email alerts
|

Financial Compass for Slovak Enterprises: Modeling Economic Stability of Agricultural Entities

Abstract: The risk of corporate financial distress negatively affects the operation of the enterprise itself and can change the financial performance of all other partners that come into close or wider contact. To identify these risks, business entities use early warning systems, prediction models, which help identify the level of corporate financial health. Despite the fact that the relevant financial analyses and financial health predictions are crucial to mitigate or eliminate the potential risks of bankruptcy, the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 58 publications
1
32
0
1
Order By: Relevance
“…Eight prediction models (seven of them developed in the same economic environment in Slovakia and the Altman´s Z score) were applied to the dataset of 3329 enterprises to compare the results with the best known bankruptcy model. The research findings confirm that the highest predictive ability of the bankruptcy prediction model is achieved in the same economic conditions and industrial sector in which they were primarily developed [17]. The theoretical aspects of financial architecture are analysed and it was found that the interpretation of this economic category is due to the existence of clear causal relationships between its constituent elements and their impact on the financial support.…”
Section: Financial-economics Analysissupporting
confidence: 64%
See 1 more Smart Citation
“…Eight prediction models (seven of them developed in the same economic environment in Slovakia and the Altman´s Z score) were applied to the dataset of 3329 enterprises to compare the results with the best known bankruptcy model. The research findings confirm that the highest predictive ability of the bankruptcy prediction model is achieved in the same economic conditions and industrial sector in which they were primarily developed [17]. The theoretical aspects of financial architecture are analysed and it was found that the interpretation of this economic category is due to the existence of clear causal relationships between its constituent elements and their impact on the financial support.…”
Section: Financial-economics Analysissupporting
confidence: 64%
“…Indebtedness indicators -They measure the share of external capital in total capital. Total indebtedness = external sources / total capital(17); Degree of self-financing = equity / total capital(18); Finance leverage = total capital / equity(19) Credit burden = bank loans and financial assistance / total capital(20); Interest coverage = (gross profit / loss + interest expense) / interest expense (21); Interest coverage with depreciation = (gross profit + interest expense + depreciation) / depreciation expense (22); Insolvency = short-termSHS Web of Conferences 9 2, 0 (2021) Globalization and its Socio-Economic Consequences 2020 3027 https://doi.org/10.1051/shsconf/20219203027 liabilities / short-term receivables (23); Financial profitability = profit / cash flow 1 (24); Cash flow I = Profit + depreciation -change in accruals on the assets side + change in accruals on equity and liabilities -changes in reserves (25); Cash flow II = Cash flow I -Change in inventory (26); Cash flow III = Change in short-term receivables (27); Cash flow IV = Cash flow III + Change in short-term payables (28) [20].…”
mentioning
confidence: 99%
“…It is why we did not include earlier periods in which the impact of the crisis was significant. (Valaskova et al, 2020) As independent variables, values of 37 financial indicators (not only ratios) calculated from real financial statements from 2016 to 2018 were used. They are presented and characterized in more details for example in Durica et al (2019).…”
Section: Background Of the Research Data And Variables Usedmentioning
confidence: 99%
“…Profit, within the result of management, represents one of the most important flow quantities. This explains how effectively corporate capital is used in the entity [6].…”
Section: Introductionmentioning
confidence: 99%